The rise of AI-assisted instructional leadership: empirical survey of generative AI integration in school leadership and management work - Berkovich, Izhak (Frontiers in Education, 2025)
This study examined the rising importance of generative artificial intelligence (GenAI) in school leadership. Research in educational leadership and management must change to keep up with how digital technology continues to influence organisational procedures and human relationships in organisations in the 21st century. The study explores two key questions: (a) at what stage of adopting innovation are school leaders currently in their use of GenAI (innovators, early adopters, early majority, late majority, or laggards) and (b) which domains of their school leadership work (managerial, instructional, social, political, or moral) are most influenced by their use of GenAI? Data were collected through an online survey of 302 Israeli school leaders (coordinators, subject heads, department heads, school counsellors, vice-principals, principals, etc.). A series of descriptive analyses were conducted to examine the research questions. The findings indicate that currently about 50% of the school leaders in the sample are at the early majority stage of adopting GenAI technology, about to cross into the late majority stage. The results also indicate the rise of AI-assisted instructional leadership above all other domains of school leadership work. Additional analyses indicate some patterns of integration and usage relate to seniority and role type. The study expands our understanding of the rapidly growing effect of GenAI in school leadership in general and AI-assisted instructional leadership in particular. These insights contribute to the limited research on GenAI’s integration into school leadership by offering some of the missing empirical evidence on the scope and direction of the phenomenon.